EDUCATION AND DEMOCRACY IN PORTUGUESE-SPEAKING AFRICAN COUNTRIES (PALOP): A PROPOSAL FOR POLITICAL TRAINING IN BASIC EDUCATION (REMUNOM, 2026)
Political instability has been the cause of several recent crises in Portuguese-speaking African countries. The colonial legacy has entrenched a system of clientelism and corruption in the culture of these countries, and it is in this context that this work aims to investigate the relationship between the education system and the current state of democracy, and how to use education as a weapon against authoritarian and autocratic governments. To achieve the stated objectives, a bibliographic and documentary methodology was used, consisting of the analysis of articles, theses, reports, and official documents to create a holistic view of the real scenario. The main findings showed that while most Portuguese-speaking African countries have very well-structured laws and education systems, these laws fail to translate into real public policies due to pressure from governments seeking to preserve their monopoly of power. On the other hand, there are populations that, for the most part, lack political education. In this context, the inclusion of Political Science as a subject from basic education onwards becomes mandatory. Only through education is it possible to create a sustainable democracy, and this education must begin in the early years of primary school.